2022
DOI: 10.1007/s00056-022-00419-1
|View full text |Cite
|
Sign up to set email alerts
|

Dreidimensionale Charakteristika der Mandibula bei skelettalen Malokklusionen

Abstract: Purpose We aimed to comprehensively analyse a possible correlation between skeletal malocclusions, gender and mandibular characteristics in all three dimensions in adults and to identify mandibular characteristics that are typical for extreme skeletal patterns. Methods A 3D model of the skull was calculated in 111 adult patients (mean age = 27.0 ± 10.2 years; 49 women, 62 men) from available computed tomography or cone beam computed tomography scans of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…Regarding the investigated variables of thickness and volume of the mandibular angle, there was no influence of the different skeletal patterns of development (skeletal malocclusions and facial types), which corroborates previous studies found in the literature [ 25 , 26 ]. In contrast, the study conducted by Olbrisch et al (2022) [ 27 ] found significant association between the different skeletal patterns of development and mandibular volume. In addition to the different methodologies applied and smaller sample size (n = 111) in relation to the present study, the authors assessed the volume of the mandibular body; thus, it is not possible to directly compare the results.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Regarding the investigated variables of thickness and volume of the mandibular angle, there was no influence of the different skeletal patterns of development (skeletal malocclusions and facial types), which corroborates previous studies found in the literature [ 25 , 26 ]. In contrast, the study conducted by Olbrisch et al (2022) [ 27 ] found significant association between the different skeletal patterns of development and mandibular volume. In addition to the different methodologies applied and smaller sample size (n = 111) in relation to the present study, the authors assessed the volume of the mandibular body; thus, it is not possible to directly compare the results.…”
Section: Discussionmentioning
confidence: 83%
“…Mandibular asymmetry is characterized by dimensional differences in size, shape, and volume of the left and right sides of the mandible, which can be the cause of aesthetic and functional problems. The imbalance in the process of craniofacial development and growth of the individual may also be associated with skeletal asymmetry [ 27 ]. Previous studies have observed that individuals with different skeletal development patterns, such as Class III malocclusion and dolichocephalic, presented higher values of skeletal asymmetry [ 7 , 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…To this extent, cone beam computed tomography (CBCT) can be used to conduct an effective evaluation of the structures of the craniofacial complex three‐dimensionally. Studies have shown the effectiveness of evaluations performed by 3D surface models constructed from CBCT, thus confirming it as an innovative tool with high accuracy, which enables measurements to be conducted in different spatial planes 14–22 …”
Section: Introductionmentioning
confidence: 81%
“…Studies have shown the effectiveness of evaluations performed by 3D surface models constructed from CBCT, thus confirming it as an innovative tool with high accuracy, which enables measurements to be conducted in different spatial planes. [14][15][16][17][18][19][20][21][22] The aim of this study was to investigate maxillomandibular morphology in hyperdivergent and hypodivergent individuals using 3D surface models. The MP angle was used as a reference 23 to define the skeletal morphology, and to separate the groups.…”
Section: Introductionmentioning
confidence: 99%
“…Management of these deformations calls for the prediction of the skeletal growth pattern to aid in the diagnosis and correction of these conditions. This integrates accurate estimation of the craniofacial growth patterns [ 10 ]. It is worth noting that malocclusions are influenced by the genetic makeup of individuals [ 9 ].…”
Section: Introductionmentioning
confidence: 99%